Disparities in Cessation Behaviors Between Hispanic and Non-Hispanic White Adult Cigarette Smokers in the United States, 2000–2015 - Babb, Stephen (Prev Chronic Dis, 2020)
INTRODUCTION: Hispanic adults make up a growing share of US adult smokers, and smoking is a major preventable cause of disease and death among Hispanic adults. No previous study has compared trends in smoking cessation behaviors among Hispanic adults and non-Hispanic white adults over time. We examined trends in cessation behaviors among Hispanic and non-Hispanic white adult cigarette smokers during 2000–2015. METHODS: Using self-reported data from the National Health Interview Survey, we compared trends in quit attempts, receipt of advice to quit from a health professional, and use of cessation treatment (counseling and/or medication) among Hispanic and non-Hispanic white adult smokers. We also assessed these behaviors among 4 Hispanic subgroups. We conducted analyses in 2018–2019. RESULTS: Past-year quit attempts increased during 2000–2015 among both non-Hispanic white and Hispanic smokers, with no significant differences between these groups. Receiving advice to quit increased significantly among non-Hispanic white adults but did not increase significantly among Hispanic adults. Cessation treatment use increased among both non-Hispanic white and Hispanic adults. Throughout 2000–2015, the prevalence of receiving advice to quit and using cessation treatments was lower among Hispanic adults than non-Hispanic white adults. In 2015, a higher proportion of Hispanic than non-Hispanic white smokers visited a health care provider without receiving advice to quit. CONCLUSION: Hispanic adult smokers are less likely to receive advice to quit and to use proven cessation treatments than non-Hispanic white smokers, and this pattern persisted over time. Culturally competent educational initiatives directed at both providers and Hispanic communities could help eliminate this marked and persistent disparity.